2012
DOI: 10.1002/pdi.1670
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors influencing non‐attendance at the diabetes clinic and service improvement strategies from patients' perspectives

Abstract: A significant number of people with type 1 diabetes do not attend their clinic appointments. This study investigated the reasons underlying this decision and explored possible service improvement strategies.This was a cross‐sectional telephone survey among all patients with type 1 diabetes missing at least one appointment at a diabetes clinic between 1 October 2009 and 30 September 2010. Patients were asked two questions: why they did not attend the appointment and how attendance could be improved.The initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…This study suggests that forgetting was a major reason for DNA and this is supported many of the studies discussed (Neal et al, 2005;Akhter et al, 2012;Killaspy et al, 2000). Other reasons for drop-out included being too physically or psychiatrically unwell, again this is well supported by the literature (Akhter et al, 2012;Killaspy et al, 2000;Lever Taylor et al, 2013). Finally, work commitments were also found to be reasons for non-attendance in studies by Hillis and Alexander, (1990) and DeFife et al (2010).…”
Section: Reasons For Non-attendancesupporting
confidence: 72%
See 2 more Smart Citations
“…This study suggests that forgetting was a major reason for DNA and this is supported many of the studies discussed (Neal et al, 2005;Akhter et al, 2012;Killaspy et al, 2000). Other reasons for drop-out included being too physically or psychiatrically unwell, again this is well supported by the literature (Akhter et al, 2012;Killaspy et al, 2000;Lever Taylor et al, 2013). Finally, work commitments were also found to be reasons for non-attendance in studies by Hillis and Alexander, (1990) and DeFife et al (2010).…”
Section: Reasons For Non-attendancesupporting
confidence: 72%
“…In general healthcare settings young men (15-44 years old) are most likely to miss appointments (ICHSC, 2006); with young men almost twice as likely to DNA compared to women of the same age (ICHSC, 2013). A history of non-attendance (Neal, Hussain-Gambles, Allgar, Lawlor and Dempsey, 2005) and poorer levels of health (Akhter, Dockray and Simmons, 2012) Improvement, 2008). In secondary care mental health settings being younger, having a history of selfharm, higher levels of social deprivation (Hillis, Alexander and Eagles, 1993), higher levels of mental disorder (Killaspy, Banerjee, King and Lloyd, 2000) and the method of invitation to the appointment (Hillis and Alexander., 1990) are all influential in determining non-attendance.…”
Section: Non-attendance and Drop-outmentioning
confidence: 99%
See 1 more Smart Citation
“…PASA is a waste of scarce resources, considering the already considerable wait times for chronic pain consultations [7]. Without the benefit of a cancellation call, PASA deprives other patients of the opportunity to schedule an appointment[8]. On the other hand, PASA may indicate barriers to healthcare[9], depriving our most vulnerable patients of needed specialized pain services[1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out by Akhter et al [16] and Barclay [17] focused on text message reminders system that encourage patients to take their medication regularly. The studies reported that mobile reminders were most helpful to reduce the number of missed medications, compared to the manual reminder systems.…”
Section: Sms Text Messagesmentioning
confidence: 99%